2020
DOI: 10.21472/bjbs(2020)071509
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of gender education on female entreprenuership: Breaking the glass ceilings for a prosperous new Nigeria

Abstract: Gender education and entrepreneurship have become worldwide phenomena for women, particularly in patriarchy societies where all kinds of discriminations, subjugation against them are frightening realities of contemporary times. As a result, female entrepreneurship has been weighed down by poor education, social norms, and lack of access to free credit facilities. It is in this context that this paper examines the impacts of gender education on female entrepreneurship in Enugu urban, Enugu state, Nigeria. A sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Consequently, some studies have asserted that lecturers' inadequacy and lack of depth in entrepreneurship knowledge is a major setback in EE implementation in Nigeria. However, very few studies have examined the link between the perceived competence of lecturers and the EI of students in HEIs in the context of Nigeria (Unachukwu, 2010;Nwambam, et al, 2018;Mamman, et al, 2018;Scent, et al, 2020;Olofinyehun, et al, 2022). Olorundare and Kayode (2014) noted that insufficient trainers have hamstrung EE in Nigeria mostly because those who facilitate EE are perceived to know little about entrepreneurship.…”
Section: Competence Of Lecturers and Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, some studies have asserted that lecturers' inadequacy and lack of depth in entrepreneurship knowledge is a major setback in EE implementation in Nigeria. However, very few studies have examined the link between the perceived competence of lecturers and the EI of students in HEIs in the context of Nigeria (Unachukwu, 2010;Nwambam, et al, 2018;Mamman, et al, 2018;Scent, et al, 2020;Olofinyehun, et al, 2022). Olorundare and Kayode (2014) noted that insufficient trainers have hamstrung EE in Nigeria mostly because those who facilitate EE are perceived to know little about entrepreneurship.…”
Section: Competence Of Lecturers and Intentionmentioning
confidence: 99%
“…In some studies, the positive effects of education on female students have been reported, but many others report little or no effect on female students' EI (Ndofirepi et al, 2018;Contreras-Barraza et al, 2021;Justus, 2021). Previous research argues that women may be discouraged from having high aspirations by gender stereotypes and may be deprived of the essential resources required to start and run their own businesses (Westhead & Solesvik, 2016;Scent et al, 2020).…”
Section: Introductionmentioning
confidence: 99%